Phosphorylation of Human Cytomegalovirus Glycoprotein B (gB) at the Acidic Cluster Casein Kinase 2 Site (Ser(900)) Is Required for Localization of gB to the trans-Golgi Network and Efficient Virus Replication - Jarvis, Michael A. (American Society for Microbiology, 2004)
Human cytomegalovirus (HCMV) glycoprotein B (gB), encoded by the UL55 open reading frame, is an essential envelope glycoprotein involved in cell attachment and entry. Previously, we identified residue serine 900 (Ser(900)) as a unique site of reversible casein kinase 2 phosphorylation in the cytoplasmic domain of HCMV gB. We have also recently shown that gB is localized to the trans-Golgi network (TGN) in HCMV-permissive cells, thereby identifying the TGN as a possible site of virus envelopment. The aim of the current study was to determine the role of Ser(900) phosphorylation in transport of gB to the TGN and in HCMV biogenesis. Recombinant HCMV strains were constructed that expressed gB molecules containing either an aspartic acid (gBAsp(900)) or alanine residue (gBAla(900)) substitution at Ser(900) to mimic the phosphorylated or nonphosphorylated form, respectively. Immunofluorescence analysis of the trafficking of gB mutant molecules in fibroblasts infected with the HCMV recombinants revealed that gBAsp(900) was localized to the TGN. In contrast, gBAla(900) was partially mislocalized from the TGN, indicating that phosphorylation of gB at Ser(900) was necessary for TGN localization. The increased TGN localization of gBAsp(900) was due to a decreased transport of the molecule to post-TGN compartments. Remarkably, the substitution of an aspartic acid residue for Ser(900) also resulted in an increase in levels of progeny virus production during HCMV infection of fibroblasts. Together, these results demonstrate that phosphorylation of gB at Ser(900) is necessary for gB localization to the TGN, as well as for efficient viral replication, and further support the TGN as a site of HCMV envelopment.